Application of Participatory Ergonomic Method to Reduce Musculoskeletal Disorders With Rapid Whole Body Assessment (REBA) at PT. Adyawinsa Stamping Industries - Sukapto, Paulus; Susanto, Sani; F. Rohman (Jurnal Improsci, 2024)
PT. Adyawinsa Stamping Industry is one of the automotive companies in Karawang, West Java. In the production process, most of the work has poor posture, which can cause VascularDisorders (MSDs). In the process of eliminating and reducing the risk of MSDs in the workplace, the level of MSD risk experienced by workers is calculated using the REBA method. The results of the REBA calculation obtained several activities with values above 9 (meaning that an improvement is needed). To improve the work system using the Participatory ergonomic (PE) method involving the operator, management and ergonomics. The results of the application of PE in helping to reduce the risk level of MSDs are engineering (making auxiliary tools and also management engineering) that can improve the work posture used, namely using the REBA method. Based on the results of the REBA calculation after the improvement, the risk generated is a risk level smaller than the previous posture, namely medium and low. Real improvements are hoped to create a safe, comfortable, and productive workplace.